Performance standards and measuring performance in Ghana - Dodoo, Robert (1997)
The Government of Ghana has recently produced draft guidelines on `Setting Targets and Measuring Performance of Implementing Agencies' within the Civil Service. This article summarizes some of the key considerations contained in the detailed draft guidelines and puts these into the context of the current reform initiatives in the Ghana Civil Service. It then outlines some of the key ideas, including the importance of employee participation and consensus building. - Reproduced
Keywords: Civil service - Ghana; Civil service